PID Control for Balancing Bike Model using Reaction Wheel - Tran, Thi-Ngoc-Tram; Ho, Thanh-Viet; Nguyen, Huu-Loi; Le, Ngoc-Nam; Tran, Van-Phuc; Tran, Quoc-Bao; Mai, Pham-Phuong; Pham, Ngoc-Duy; Bui, Tien-Phat; Le, Thi-Hong-Lam (Journal of Fuzzy Systems and Control, 2024)
Motorcycles or bicycles are known as unbalanced systems like the inverted pendulum model. Normally, we must use a handlebar to control the Motorcycles or bicycles. In this paper, the authors propose a PID controller for a balance bike using a reaction wheel. The authors formulated a mathematical model for the system and performed simulation testing using MATLAB to control it. Also, the simulation model of the balance bike system using a reaction wheel has been developed to assess the feasibility of building and controlling the system without relying on its mathematical model. The study will explicitly provide the performance of the PID algorithm in controlling a balanced bike using a reaction wheel.